Distribution of Aspergillus flavus in soil and air of agricultural fields - P.L. SINGH, S.K. AHMAD and (Indian Phytopathology, 2002)
Soil and air of agricultural fields situated at Bhagalpur, Bihar State, India were scanned for distribution of Aspergillus flavus and other moulds. Qualitative spectrum of fungal population of these two systems (soil and air) was much different. There was abundance of A. flavus in soi I samples, while in air Cladosporium, Curvularia, Fusarium and Alternaria spp. was dominating. Soil types differred in their capability of harbouring A. flavus; usually loamy soil with rich organic matter created more congenial condition for growth of A. flavus, while it was less favourable in sandy soils with reduced organic carbon. Wet and warm season of September was most suitable for A. flavus but even in this month, only a slight rise in its aerial density was observed. A total number of 321 and 61 isolates of A flavus obtained from soil and air were screened for their toxigenicity, of which 57 and 50 per cent strains were aflatoxin producers. Most of the isolates were producing only aflatoxin BI or BI and B2; only 33 isolates out of 184 toxigenic strains were producing 01. or 01 and O2 both alongwith BI and B2. These results demonstrate that soil represents a more stable ecosystem in which A. flavus successfully sustains itself while the aerial environment have to contend with extremes of environmental variations that makes the condition unsuitable for A. flavus.